Review Strategis Upaya Pengamanan Laut Nasional Menuju Keamanan Maritim dan Pengelolaan Ruang Laut Indonesia - Suharyo, Okol Sri; Bastari, Avando (Rekayasa, 2021)
The Republic of Indonesia as a world maritime country and an archipelagic country which has 17,504 islands whose territorial area is dominated by the ocean. As a maritime country, Indonesia has 4 (four) points that become international chokepoints, namely the Malacca Strait, Sunda Strait, Lombok Strait and the Ombai-Wetar Strait. Indonesia has established three Indonesian Archipelagic Sea Lanes (ALKI) for the peaceful passage of international shipping, which are guaranteed by international and national law. The Indonesian Maritime Security Agency is a Non-Ministerial State Institution whose position is under and directly responsible to the President and has the authority to enforce the law at sea and is justified by law, so that with the issuance of Law Number 32 of 2014 concerning Marine Affairs and Presidential Regulation Number 178 of 2014 concerning the Indonesian Maritime Security Agency, it can be interpreted that there is legal legitimacy for the Indonesian Maritime Security Agency in carrying out its duties, functions and authorities to carry out law enforcement against special crimes at sea. This study aims to explore Indonesia's strategic role in law enforcement at sea towards national maritime security and resilience. The method used is a literature study approach and the data analysis technique used is a qualitative data approach by conducting secondary data analysis to explain the findings obtained. This research produces findings in the form of an analysis of Indonesia's strategic role in law enforcement at sea towards maritime resilience and security both nationally and regionally.